Engineering Applications of Computational Fluid Dynamics - Shaari, Ku Zilati Ku.; Shaari, Ku Zilati Ku.; Awang, Mokhtar.; Awang, Mokhtar. (Advanced Structured Materials, 2015)
This volume presents the results of Computational Fluid Dynamics (CFD) analysis that can be used for conceptual studies of product design, detail product development, process troubleshooting. It demonstrates the benefit of CFD modeling as a cost saving, timely, safe and easy to scale-up methodology.